Bivariate flow cytometric analysis and sorting of different types of maize starch grains. Issue 2 (4th October 2017) - Zhang, Xudong; Feng, Jiaojiao; Wang, Heng; Zhu, Jianchu; Zhong, Yuyue; Liu, Linsan; Xu, Shutu; Zhang, Renhe; Zhang, Xinghua; Xue, Jiquan; Guo, Dongwei
Abstract: Particle‐size distribution, granular structure, and composition significantly affect the physicochemical properties, rheological properties, and nutritional function of starch. Flow cytometry and flow sorting are widely considered convenient and efficient ways of classifying and separating natural biological particles or other substances into subpopulations, respectively, based on the differential response of each component to stimulation by a light beam; the results allow for the correlation analysis of parameters. In this study, different types of starches isolated from waxy maize, sweet maize, high‐amylose maize, pop maize, and normal maize were initially classified into various subgroups by flow cytometer and then collected through flow sorting to observe their morphology and particle‐size distribution. The results showed that a 0.25% Gelzan solution served as an optimal reagent for keeping individual starch particles homogeneously dispersed in suspension for a relatively long time. The bivariate flow cytometric population distributions indicated that the starches of normal maize, sweet maize, and pop maize were divided into two subgroups, whereas high‐amylose maize starch had only one subgroup. Waxy maize starch, conversely, showed three subpopulations. The subgroups sorted by flow cytometer were determined and verified in terms of morphology and granule size by scanning electron microscopy and laser particle distribution analyzer. Results showed that flow cytometry can be regarded as a novel method for classifying and sorting starch granules. © 2017 International Society for Advancement of Cytometry